Can Crypto Currencies Challenge Sovereign Currencies? A Multidisciplinary Overview of Opportunities and Risks - Sadok, Hicham; El Hadi El Maknouzi, Mohammed (International Journal of Criminology and Sociology, 2025)
Considered as a niche phenomenon, a kind of technological folklore, which could disappear overnight, cryptocurrency has been the subject of few multidisciplinary analyses to understand how a series of numbers, supported by no power to impose its use, could constitute a currency? The review of the available literature reveals a state of knowledge scattered in the different disciplines that are interested in it. The objective of this article is to remedy this by aggregating essential historical, economic, legal and technological knowledge developed in the study and analysis of this technical-financial innovation. The aim is to examine the opportunities, challenges and risks of using cryptocurrencies as an alternative to sovereign currency, through a nuance between the optimism of those who see in cryptocurrencies liberation from the monetary constraints of States, and the hostility of those who see in these innovations a utopian monetary system or a lever of incitement to crime. A concluding discussion will expose the trend and some recommendations for supporting eventual implementation with the least criminogenic effect.